2012
DOI: 10.1016/j.imlet.2012.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of IgG subclasses (IgG1 and IgG3) to recombinant SAG2A protein from Toxoplasma gondii in sequential serum samples from patients with toxoplasmosis

Abstract: The kinetics of the humoral immune response was evaluated using the recombinant SAG2A protein comparatively to soluble Toxoplasma antigen (STAg) by ELISA in sequential serum samples of patients with toxoplasmosis up to 12 months of illness onset. The follow up of IgM and IgA levels to STAg showed a gradual decrease, with the majority of patients (88%) seropositive for IgM up to 12 months of infection, whereas IgA seropositivity was relatively low (78%) compared to IgM (100%) in the first 3 months of infection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
1
14
0
8
Order By: Relevance
“…Our present work locates a previously predicted B cell linear epitope [18] within this predicted IUP domain of SAG2A, which corroborates with our previous studies on immunodominance of the protein and its potential as an acute phase marker for the diagnosis of human toxoplasmosis [32,33,54]. In addition, we show here that recombinant SAG2A was able to specifically detect T. gondii -induced antibodies in experimental and natural infections eliminating potential serological cross-reactivity with closely related N. caninum , a long-lived setback within the veterinary field [55-57].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our present work locates a previously predicted B cell linear epitope [18] within this predicted IUP domain of SAG2A, which corroborates with our previous studies on immunodominance of the protein and its potential as an acute phase marker for the diagnosis of human toxoplasmosis [32,33,54]. In addition, we show here that recombinant SAG2A was able to specifically detect T. gondii -induced antibodies in experimental and natural infections eliminating potential serological cross-reactivity with closely related N. caninum , a long-lived setback within the veterinary field [55-57].…”
Section: Discussionsupporting
confidence: 91%
“…ELISA and Western blotting protocols using recombinant SAG2A (rSAG2A) were performed for the detection of IgG antibodies present in serum samples of experimentally infected mice and naturally infected goats to T. gondii and N. caninum , as previously described [32,33]. Antibody titers were expressed as ELISA index (EI), according to the following formula: EI = OD sample/OD cut off, as described elsewhere [34].…”
Section: Methodsmentioning
confidence: 99%
“…antibodies, IgA, IgG subclasses, saliva, Toxoplasma gondii Some years ago, specific abs of several IgG subclasses were studied using serum samples from patients with acquired infections. [17][18][19] The main finding was that IgG1 abs were predominant and longlasting. More recently, we and other groups have found that specific serum IgG subclasses are useful to confirm congenital infection and may be associated with clinical problems in the newborns.…”
Section: Introductionmentioning
confidence: 99%
“…IgG ELISAs using recombinant SAG2A were recently shown to be sensitive (95%) and specific (100%) compared to the crude Toxoplasma antigen ELISA (23, 24). In this work, we demonstrate that a bead coupled with recombinant SAG2A protein can be incorporated into our neglected tropical disease (NTD) MBA panel and used to determine Toxoplasma seroprevalence.…”
Section: Introductionmentioning
confidence: 99%